Automotive price reduced (Perodua); Factors that contribute the sale of automobile: The case of Perodua Alamesra Kota Kinabalu / Nurhamidah Kaharuddin - Kaharuddin, Nurhamidah (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2014)
The purpose of conducting this research is to fulfill the syllabus of MKT669 in order for the University award the Bachelor Degree. The Researcher came out in conducting a research entitled of Automotive Price Reduced (Perodua); Factors That Contribute the Sales of Automobile: The Case of Perodua Alamesra Kota Kinabalu. In the end of this research project, the Researcher may conclude that the most of the customer preferred to buy imported car rather than national car due to the quality offered by the imported car. However, majority of the customer agreed that Perodua offer the best and affordable price for each models such as Myvi, Viva and Alza. Furthermore, the policy introduced by the government reduced the burden of the customer for them to have own car. In a conclusion, from the research conducted, the Researcher also found out that Perodua have conducted the government initiative in reducing the car price. The initiative give positive impact in economy especially for low income.